(untitled) (Revista de Educação Pública, 2012)
Conselho Editorial Bernardete A. GATTI Fundação Carlos Chagas – São Paulo/SP Celso de Ruy BEISIEGEL USP – São Paulo/SP Christian ANGLADE University of Essex - Inglaterra Florestan FERNANDES (in memorian) Francisco Fernández BUEY Universitat Pompeu Fabra – Espanha Jean HÉBETTE UFPA – Belém/PA Maria de Lourdes BANDEIRA UFMTCuiabá/ MT Martin COY Univ. Tubingen – Alemanha Moacir GADOTTI USP – São Paulo/SP Nicanor Palhares SÁ UFMT – Cuiabá/MT Paolo NOSELLA UFSCar – São Paulo/SP Paulo SPELLER UFMT- Cuiabá/MT Walter E. GARCIA CNPq – Brasília/DF